Mechanistic Insights Into Overloading-Induced Terminal Differentiation of TMJ Condylar Cartilage at the Single Cell Level - Zhou, Dian; Jiang, Yiling; Li, Yingcui; Zeng, Huanyu; Li, Xinchun; He, Yufang; Wang, Xin; Liang, Yiteng; Parizek, Vojtech; Liu, Ousheng; Tang, Zhangui; Zhou, Yueying (Smart medicine, 2025)
The incidence of temporomandibular joint (TMJ) degeneration has been steadily increasing, with overloading identified as a major risk factor. This condition often leads to condylar cartilage degeneration, significantly affecting patients' quality of life; however, the molecular mechanisms underlying this process remain poorly understood, and effective treatments are still lacking. We utilized single-nucleus RNA sequencing to analyze the condylar cartilage in an overloading mouse model. This approach enabled the identification of 11 distinct cell types within the condylar chondrocytes. Through the application of pseudotime trajectory Analysis and cellchat analyses, we identified the key gene Acvr1b and its associated signaling pathway, which are crucial for regulating the terminal differentiation of condylar chondrocytes. This study utilized single-nucleus RNA sequencing and in vitro validation to investigate the role of Acvr1b in TMJ cartilage degeneration under overloading stress. Our findings reveal key pathways involved in chondrocyte differentiation, providing a theoretical basis for the development of targeted therapeutic interventions.
Keywords: Acvr1b; single cell; terminal differentiation; temporomandibular joint; condylar cartilage